2017
DOI: 10.1161/jaha.117.005648
|View full text |Cite
|
Sign up to set email alerts
|

Calcification and Oxidative Modifications Are Associated With Progressive Bioprosthetic Heart Valve Dysfunction

Abstract: BackgroundBioprosthetic heart valves (BHVs), fabricated from glutaraldehyde‐pretreated bovine pericardium or porcine aortic valves, are widely used for the surgical or interventional treatment of heart valve disease. Reoperation becomes increasingly necessary over time because of BHV dysfunction.Methods and ResultsForty‐seven explanted BHV aortic valve replacements were retrieved at reoperation for clinically severe BHV dysfunction over the period 2010–2016. Clinical explant analyses of BHV leaflets for calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
0
39
0
4
Order By: Relevance
“…Inflammatory cell aggregates in BHVs tend to be surface oriented, which is reflected by the hematoxylin counterstain of rat explants. It is possible that AGE formation in BHVs provides the opportunity for RAGE signaling and macrophage deposition to produce reactive oxygen species (ROS) that result in OxAA formation in BHV, as demonstrated by our group in both experimental and clinical BHV studies 5,57 . The lack of demonstrable glucosepane in the rat subcutaneous explants versus virtually all the clinical explants may be due to short (30-day) implantation times relative to the physiologic formation time of glucosepane, which proceeds through long-lived Amadori intermediates 12,53,58 .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Inflammatory cell aggregates in BHVs tend to be surface oriented, which is reflected by the hematoxylin counterstain of rat explants. It is possible that AGE formation in BHVs provides the opportunity for RAGE signaling and macrophage deposition to produce reactive oxygen species (ROS) that result in OxAA formation in BHV, as demonstrated by our group in both experimental and clinical BHV studies 5,57 . The lack of demonstrable glucosepane in the rat subcutaneous explants versus virtually all the clinical explants may be due to short (30-day) implantation times relative to the physiologic formation time of glucosepane, which proceeds through long-lived Amadori intermediates 12,53,58 .…”
Section: Discussionmentioning
confidence: 82%
“…This process is driven by cellular, biochemical, and biomechanical mechanisms arising from valve properties and design, patient characteristics, and the interactions between them. Calcification is observed in the majority of SVD cases; however, approximately 30% of SVD cases are not associated with significant calcification [5][6][7] . Further, recent observation suggests that calcification might be associated with SVD without necessarily being functionally causative 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A) 14 C-glucose (100mM) uptake by BP with and without the presence of BSA (5%). * p<0.001 B) 14 C-glucose (100mM) uptake by CS with and without the presence of BSA (5%).…”
Section: Figure 1 Glycation Of Glutaraldehyde Pretreated Bovine Perimentioning
confidence: 99%
“…However, this yielded only incremental improvements in BHV lifespan [10][11][12][13]. Prior studies of explanted BHV showed that the degree of calcification does not completely explain SVD, and that approximately 25% of failed valves lack any significant calcification [14].…”
mentioning
confidence: 99%